The machine learning in the prediction of elections - M.S.C. José A. León-Borges; M.A. Roger-Ismael-Noh-Balam; Lic. Lino Rangel Gómez; Br. Michael Philip Strand (ReCIBE)
This research article, presents an analysis and a comparison of three different algorithms: A.- Grouping method K-means, B.-Expectation a convergence criteria, EM and C.- Methodology for classification LAMDA, using two software of classification Weka and SALSA, as an aid for the prediction of future elections in the state of Quintana Roo. When working with electoral data, these are classified in a qualitative and quantitative way, by such virtue at the end of this article you will have the elements necessary to decide, which software, has better performance for such learning of classification.